Design and Analysis of High Performance 2D Photonic Crystal Based Sensors for Biomedical Sensing Applications - Bouguerra Yaaqoub; Zouaoui Faiz; ENC/ Harhouz Ahlam (University of M'sila, 2024)
EN Nowadays, the research on the design and development of wearable label-free biosensors with their potential in human health monitoring has experienced a very rapid growth because of the need to develop high-performing methods to detect and measure low concentrations of specific molecules in various fields. Among all the methods proposed, photonic crystals (PhCs) structures are on focus and offers a good alternative due to their high sensitivity, biocompatibility traits, the capability to control and manipulate the flow of light and enhance field-matter interaction, and the ability to integrate with other electrical components easily. Much attention has been drawn to PhCs biosensors to detect the analyte because of their inherent compactness, high sensitivity, high selectivity, and low cost. In this master's thesis, a novel photonic crystal biosensor based on a two-dimensional photonic crystal (2D-PhC), geared towards rapid biomedical diagnostics at the point-of-care, is proposed and simulated based on refractive index changes of the analyte. The proposed design is simulated using Plane Wave Expansion (PWE) method and Finite-Difference Time-Domain (FDTD) algorithm. The high performance and simple design of the proposed biosensor make it a suitable candidate for bio-sensing applications. In this context, the work of this master's thesis will consist in studying the sensing performance and evaluating the potentialities of biosensors based on photonic crystals using the RSoft-CAD software.
Keywords: PhC Biosensor; Sensitivity; Q-Factor; Refractive Index; RSoft-CAD; FDTD.